Distribution and abundance of phlebotominae, vectors of leishmaniasis, in Argentina: spatial and temporal analysis at different scales - Quintana, María Gabriela (2012)
Fil: Quintana, María Gabriela. Universidad Nacional de Tucuman. Facultad de Ciencias Naturales. Instituto Superior de Entomología; Argentina.